2014
DOI: 10.1158/1078-0432.ccr-13-1862
|View full text |Cite|
|
Sign up to set email alerts
|

Mesothelin Overexpression Is a Marker of Tumor Aggressiveness and Is Associated with Reduced Recurrence-Free and Overall Survival in Early-Stage Lung Adenocarcinoma

Abstract: Purpose In an effort to identify molecular markers of tumor aggressiveness and therapeutic targets in lung adenocarcinoma (ADC), we investigated the expression of mesothelin (MSLN) in lung ADC, as well as its biological and clinical relevance. Experimental Design In a training and validation set of patients with early-stage (I–III) lung ADC (n=1209), a tissue microarray consisting of tumors and normal lung tissue was used to examine the association between MSLN expression and recurrence-free survival (RFS) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 28 publications
8
133
1
Order By: Relevance
“…One key issue with solid tumours is that the inherent tumour heterogeneity is likely to be a substantial barrier to identifying an optimal target, and relatedly, antigen loss will probably be a key factor precluding curative remissions. Indeed, antigen density (as mentioned above regarding ALK in neuroblastoma cells 118 ) and inherent tumour heterogeneity in antigen expression in solid tumours (for example, mesothelin 154 , HER2 (ref. 155 ) or MUC1 (ref.…”
Section: Car T Cell Strategies Beyond B Cell Targeting Cd19mentioning
confidence: 99%
“…One key issue with solid tumours is that the inherent tumour heterogeneity is likely to be a substantial barrier to identifying an optimal target, and relatedly, antigen loss will probably be a key factor precluding curative remissions. Indeed, antigen density (as mentioned above regarding ALK in neuroblastoma cells 118 ) and inherent tumour heterogeneity in antigen expression in solid tumours (for example, mesothelin 154 , HER2 (ref. 155 ) or MUC1 (ref.…”
Section: Car T Cell Strategies Beyond B Cell Targeting Cd19mentioning
confidence: 99%
“…(27) These observations correlate with clinical observations showing that MSLN expression, as well as elevated serum SMRP levels, are associated with progressing tumor burden, increasing stage, and poor overall survival. (2224, 28, 29) Cancer cells that possess an invasive phenotype express high amounts of membranous MSLN, rather than the cytoplasmic form. (30, 31) Our group(22) and others(29) have reported that in patients with lung adenocarcinoma, MSLN is expressed at metastatic sites, and correlates with tumor aggressiveness and KRAS mutation.…”
Section: Msln Functionmentioning
confidence: 99%
“…22 MSLN is expressed by many solid tumors, with particularly robust expression in mesothelioma, epithelial ovarian cancer, and pancreatic adenocarcinoma (Table 1). Higher expression of MSLN has been correlated with poorer prognosis for patients with ovarian cancer, 35 cholangiocarcinoma, 41,42 lung adenocarcinoma, 8,9 triple-negative breast cancer, 10,45 and resectable pancreatic adenocarcinoma. 32,33 In the neoplastic setting, MSLN is known to bind to the ovarian cancer antigen MUC16 (cancer antigen 125).…”
Section: Mslnmentioning
confidence: 99%
“…8,9,25,30,36 Recent studies have identified MSLN expression in more than 50% of both early-stage and advanced lung adenocarcinomas. Kachala et al 9 found MSLN expression in 69% of early-stage (stages I to III) lung adenocarcinomas, with approximately 20% of patients strongly expressing MSLN. Thomas et al 8 observed MSLN expression in 53% of advanced (stages IIIB to IV) lung adenocarcinomas, with high expression found in approximately 25% of patients.…”
Section: Non-small-cell Lung Cancermentioning
confidence: 99%